2009
DOI: 10.1007/s11547-009-0475-6
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory breast cancer: MR imaging findings

Abstract: The most characteristic MR findings of IBC are skin thickening, oedema, architectural distortion, mass-like enhancement with washout curve and axillary lymphadenopathy; less frequent ones are nipple retraction, mass-like enhancement and internal mammary lymphadenopathy. Prepectoral fluid is frequent but is not a sign of infiltration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
5
1
1
Order By: Relevance
“…MRI is highly sensitive for depicting primary breast parenchymal lesions and global skin abnormalities that may help diagnose inflammatory breast cancer. Lesions that were either heterogeneous or inhomogeneous, consisting of a reticular or dendritic internal enhancement with a washout or plateau kinetic curve, were commonly noted [26][27][28][29]. This is different from our findings in non-puerperal mastitis.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…MRI is highly sensitive for depicting primary breast parenchymal lesions and global skin abnormalities that may help diagnose inflammatory breast cancer. Lesions that were either heterogeneous or inhomogeneous, consisting of a reticular or dendritic internal enhancement with a washout or plateau kinetic curve, were commonly noted [26][27][28][29]. This is different from our findings in non-puerperal mastitis.…”
Section: Discussioncontrasting
confidence: 96%
“…These aforementioned manifestations in non-puerperal mastitis are slight or rare [8]. Inflammatory breast cancer usually affects females of approximately 50 years old [26,27], but non-puerperal mastitis is more common in females under 40 [5,10,11,13]. MRI is highly sensitive for depicting primary breast parenchymal lesions and global skin abnormalities that may help diagnose inflammatory breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010 Carbognin et al reported features of inflammatory breast cancer on MRI. They reported a hypertrophic IMA in 21 % of the patients [17]. In healthy persons the breast is mainly perfused by the IMA [11].…”
Section: Discussion and Further Perspectivesmentioning
confidence: 99%
“…All authors contributed to the manuscript revision and approved the submitted version. [19] 664 (17) 2248 561093 (27) 56 [19] 561 (18) 1729 56792 (26) 56 [17] 1112 (18) 358 59140 (23) 56 [19] 157 (18) 467 55229 (27) .011 ¶ (31) 512 (13) 1872 47387 (10) 946 (31) 345 (11) 1473 48318 (10) 200 (33) 83 14282 4645 7285 (33) 91 (11) 395 4682 (10) .14 † 1181 2938 12056 51175 (4) 438 14822 (27) 27 11642 53153 (5) 106 (17) 160 263 (<1)…”
Section: Discussionmentioning
confidence: 99%
“…[17] IBC is characterized by either diffused or localized radiographic density. [18] In most cases, the sign and symptoms of IBC will appear within a 6-month period. [19] The expression of different cell growth and apoptosis related markers on the surface of IBC cells play an important role in disease prognosis and management.…”
Section: Pathophysiology and Classification Of Ibcmentioning
confidence: 99%